Food apps took a free ride on the first phase of the Covid-19 pandemic in Brazil - Michele Bittencourt Rodrigues; Juliana de Paula Matos; Paula Martins Horta (Demetra)
Objective: Analyze the marketing content posted by three online food delivery (OFD) companies in Brazil on their official accounts on Facebook, Instagram, and YouTube during the first phase of the COVID-19 pandemic. Methods: Exploratory study carried out between March 20 and June 26, 2020. Posts made by these companies were coded according to the interactive tools employed and the product type shown in the posts. A thematic analysis of the posts followed seven steps. Results: A total of 137 posts were analyzed. Instagram posts represented 51.0% of the total, Facebook (40.5%), and YouTube (8.5%). More than a third of the posts showed images of foods, mainly meals predominantly made with ultra-processed foods (58.1%) and traditional meals or pasta (44.2%). Six main categories emerged from the thematic analysis: branding (83.2%); information related to the Covid-19 pandemic: measures and new functionalities (79.6%); stay at home, stay safe and take care of yours: we will make it happen (67.1%); corporate social responsibility (39.4%); individual social responsibility (34.3%); and premium offers (5.1%). Conclusion: The results indicated that the OFD companies promoted unhealthy eating and traditional meals during the first phase of the Covid-19 pandemic and used the health crisis to adjust their marketing content and promote themselves.